Preparation and structural analysis of fucomannogalactan and β-1,6-glucan from Grifola frondosa mycelium - Geng, Jie; Wang, Guining; Guo, Jiao; Han, Xiao; Qu, Yunhe; Zhou, Yifa; Tai, Guihua; Sun, Lin; Cheng, Hairong (Frontiers in Chemistry, 2023)
Introduction: Polysaccharides, key components present in Grifola frondosa, can be divided into those derived from fruiting bodies, mycelium, and fermentation broth based on their source. The structure of G. frondosa fruiting body-derived polysaccharides has been fully characterized. However, the structure of G. frondosa mycelium-derived polysaccharides remains to be elucidated. Methods: In this study, we obtained mycelia from G. frondosa by liquid fermentation and extracted them with water and alkaline solution. Then, the mycelia were isolated and purified to obtain homogeneity and systematically characterized by methylation and FT infrared (FT-IR) and nuclear magnetic resonance (NMR) spectroscopy. Results and discussion: Structural analysis showed that two neutral fractions (WGFP-N-a and AGFP-N-a1) have a common backbone composed of α-1,6-D-Me-Galp and α-1,6-D-Galp that were substituted at O-2 by 1,2-Manp, α-1,3-L-Fucp, and α-T-D-Manp and thus are identified as fucomannogalactans. WGFP-A-a, AGFP-A-b, and AGFP-A-c are β-1,6-glucans with different molecular weights and are branched with β-1,3-D-Glcp and T-D-Glcp at the O-3 of Glc. Our results provide important structural information about G. frondosa mycelium-derived polysaccharides and provide the basis for their further development and application.